Accumulation of Zn, Cu, Fe, Mn and Pb due to brick manufacturing in agricultutral soils and plants (Dhaka University Journal of Biological Sciences, 2016)
Experiment was carried out to assess the concentration of Zn, Cu, Pb, Fe and Mn in agricultural soil and plant near selected brick kilns. Soils and plants samples were collected from four points such as 250, 500, 1000 and 1500 m away from brick kilns. Three metals were found at elevated levels in the soils near brick kilns such as, Pb (92.5 to 214 mg/kg), Zn (86 to 156 mg/kg) and Cu (24.7 to 46.9 mg/kg). It may be caused due to burning of poor quality coal and fire woods. The uptake of heavy metals in the nearest areas (250 m) of the brick kilns was significantly higher than the areas far from the brick production and their concentrations range from 7 to 543 mg/kg for Pb, 23 to 101 mg/kg for Zn, 10 to 41 mg/kg for Cu, 35 to 1309 mg/kg for Fe and 26 to 126 mg/kg for Mn. Results indicated that soils and plants accumulated maximum amount of micronutrients within 500 to 1000 m distance from brick kilns significantly decreased with distance. Iron and manganese were not polluting the soils near brick kilns but affecting the plants. Therefore, it can be suggested that no agricultural crops should be grown within 1000 m distance from a brick kiln.Dhaka Univ. J. Biol. Sci. 25(1): 75-81, 2016